The Role of University Library in the Development of Information Culture of Students Studying Journalism - A. D. Mershieva (Библиосфера)
The article is devoted to identifying the role of a university library in the formation of professional competencies of students studying journalism. The relevance lies in the reduction of information competencies of mass media specialists, which affects not only the quality of information flows, but also the development of the audience, contributing to the creation and spread of misconceptions and factual errors.The purpose of the study is to determine the degree of influence of the library on the formation of elements of information culture among students in the direction of training “Journalism”. The author identifies the main problems that arise when students work with library technologies, and presents ways to solve them. The author implemented an experiment on the formation of the foundations of library and information literacy in the context of developing professional reading skills, and presented recommendations for conducting classes with first-year students. This study may be of interest to teachers who train specialists in the field of mass media, for employees of university libraries, as well as for specialists working with juniors in the framework of career guidance projects.